2019
DOI: 10.1111/1541-4337.12513
|View full text |Cite
|
Sign up to set email alerts
|

Induction, detection, formation, and resuscitation of viable but non‐culturable state microorganisms

Abstract: The viable but nonculturable (VBNC) state has been recognized as a strategy for bacteria to cope with stressful environments; in this state, bacteria fail to grow on routine culture medium but are actually alive and can resuscitate into a culturable state under favorable conditions. The VBNC state may pose a great threat to food safety and public health. To date, more than 100 VBNC microorganism species have been proven to exist in fields of food safety, environmental application, and agricultural diseases. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 290 publications
1
110
1
5
Order By: Relevance
“…Previous studies of cave communities (e.g., Bhullar et al, 2012) have resuspended samples in sterilized water obtained from that cave. Although this may improve culturability by making sample suspensions geochemically similar to the cave environment (e.g., Zengler, 2009;Stewart, 2012), osmotic stress and low salinity have been shown to induce a viable but non culturable state in bacteria (Gin & Goh, 2013;Li et al, 2014;Dong et al, 2020). This suggests that suspension solutions buffered to physiological conditions (for example, pH, sodium, and potassium; Kobayashi, 1985;Padan et al, 2005) may be effective for increasing culturability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of cave communities (e.g., Bhullar et al, 2012) have resuspended samples in sterilized water obtained from that cave. Although this may improve culturability by making sample suspensions geochemically similar to the cave environment (e.g., Zengler, 2009;Stewart, 2012), osmotic stress and low salinity have been shown to induce a viable but non culturable state in bacteria (Gin & Goh, 2013;Li et al, 2014;Dong et al, 2020). This suggests that suspension solutions buffered to physiological conditions (for example, pH, sodium, and potassium; Kobayashi, 1985;Padan et al, 2005) may be effective for increasing culturability.…”
Section: Introductionmentioning
confidence: 99%
“…Our metabolism‐based method is also promising to study slow‐growing bacteria, because they do not grow normally to form colony but still have their metabolic activity. [ 43 ] On the other hand, since our detection mechanism is different from the conventional approaches, it is beneficial for developing new drugs with brand‐new antimicrobial mechanisms. Furthermore, in the view of the potential imaging capabilities of this conjugated polymer, [ 44 ] it also holds great promise for in vivo imaging and diagnosis of infectious disease.…”
Section: Resultsmentioning
confidence: 99%
“…The virulence of VBNC pathogens can be maintained or recovered after resuscitation (Zhao, Zhong, Wei, Lin, & Ding, 2017). It has been reported that several Salmonella species can enter the VBNC state and regain culturability once the environmental conditions are back to normal (Dong et al., 2020; Ferro, Amorico, & Deo, 2018). Hence, differentiating VBNC Salmonella from the dead ones is essential for prevention of outbreaks.…”
Section: Challenges In the Development Of Salmonella Biosensorsmentioning
confidence: 99%